Conditioned taste aversion memory extinction temporally induces insular cortical BDNF release and inhibits neuronal apoptosis - Liu DW (Dove Medical Press, 2019)
Dian-Wei Liu,1,* Ling Ma,2,* Xu-Hua Zhang,2 Yun-Yan Wang31Department of Neurosurgery, Jinan Central Hospital Affiliated to Shandong University, Jinan, Shandong 250013, People’s Republic of China; 2Department of Clinical Laboratory, The Second Hospital of Shandong University, Jinan, Shandong 250033, People’s Republic of China; 3Department of Neurosurgery, QiLu Hospital of Shandong University, Jinan, Shandong 250012, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yun-Yan WangDepartment of Neurosurgery, QiLu Hospital of Shandong University, No. 44 Wen Hua Xi Road, Jinan, Shandong 250012, People’s Republic of ChinaTel +86 5 311 370 892 8040Fax +86 5 318 569 5463Email wyyqlh123@163.comBackground: Memory extinction has been reported to be related to psychiatric disorders, such as post-traumatic stress disorder (PTSD). Secretion and synthesis of brain-derived neurotrophic factor (BDNF) have been shown to temporally regulate various memory processes via activation of tropomyosin-related kinase B (TrkB) receptors. However, whether memory extinction induces the synthesis and secretion of BDNF on the basis of its localization is not understood. In this study, we aim to investigate activity-dependent BDNF secretion and synthesis in the insular cortex (IC) in the setting of conditioned taste aversion (CTA) memory extinction.Materials and methods: Rats were subjected to CTA memory extinction and BDNF antibody (or the equal volume of vehicle) was microinjected into the IC immediately after the extinction testing. Real-time polymerase chain reaction and in situ hybridization were used to detect the gene expression of BDNF, NGF and NT4. The protein levels of BDNF were determined through the enzyme-linked immunosorbent assay. In addition, the levels of phosphorylated TrkB normalized to total TrkB were evaluated using immunoprecipitation and immunoblotting. c-Fos, total extracellular signal-regulated kinase (Erk), phosphorylated Erk, and apoptosis-related protein (caspase-3), were detected by Western blotting.Results: We found that blocking BDNF signaling within the IC disrupts CTA extinction, suggesting that BDNF signaling in the IC is necessary for CTA extinction. Increased expression levels of c-Fos indicate the induced neuronal activity in the IC during CTA extinction. In addition, temporal changes in the gene expression and protein levels of BDNF in the IC were noted during extinction. Moreover, we found that phosphorylation of TrkB increased prior to the enhanced BDNF expression, suggesting that CTA extinction induces rapid activity-dependent BDNF secretion in the IC. Finally, we found decreased expression of caspase-3 in the IC after CTA extinction.Conclusion: These results demonstrate that CTA memory extinction temporally induces the release and synthesis of BDNF in the IC and inhibits neuronal apoptosis.Keywords: brain derived neurotrophic factor, insular cortex, conditioned taste aversion, secretion, apoptosis